(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Building scalable and secure Industrial IoT (IIoT) system is the need of the hour in Industrial 4.0. However, existing IIoT systems are vulnerable to a single point of failure and malicious attacks. To address the security and efficiency issues of the massive IIoT data, blockchain is widely considered as a promising solution to enable data storing, processing, and sharing in a secure and efficient way